2010
DOI: 10.1007/s12275-010-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria strains with ornithine producing capacity from natural sea salt

Abstract: Two lactic acid bacteria (LAB) having ornithine-producing capacity were isolated from Korean natural sea salt. They were Gram-positive, short rod-type bacteria, and able to grow anaerobically with CO(2) production. The isolates grew well on MRS broth at 30-37 degrees C and a pH of 6.5-8.0. The optimum temperature and pH for growth are 37 degrees C and pH 7.0. The isolates fermented D-ribose, D-galactose, D-lactose, D-maltose, Dcellobiose, D-tagatose, D-trehalose, sucrose, D-melezitose, gentiobiose, D-glucose b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 14 publications
0
32
0
4
Order By: Relevance
“…Elevated levels of serum TNF‐α and IL‐6 have been shown to inhibit the insulin signaling pathway, leading to insulin resistance . TNF‐α not only acts as a potent negative regulator of adipocyte differentiation but also decreases the expression of adipocyte‐specific genes in mature adipocytes . TNF‐α levels are increased in adipose tissue of obese rodents and humans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of serum TNF‐α and IL‐6 have been shown to inhibit the insulin signaling pathway, leading to insulin resistance . TNF‐α not only acts as a potent negative regulator of adipocyte differentiation but also decreases the expression of adipocyte‐specific genes in mature adipocytes . TNF‐α levels are increased in adipose tissue of obese rodents and humans .…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study, we reported that Lactobacillus plantarum LG42 isolated from gajami sik‐hae inhibits adipogenesis in 3T3‐L1 adipocytes, as well as decreasing intracellular triglyceride content . In addition, various clinically important amino acids such as γ‐aminobutyric acid (GABA) and ornithine are produced as a result of active growth of LAB during fermentation and storage of kimchi . Among Lactobacillus species, Lactobacillus brevis is a functional probiotic strain with peculiar biochemical features, closely related to the activity of arginine deiminase.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, each Keem sample showed presence of more than 57 9 10 6 cfu/g of LAB comprising Weissella paramesenteroides, Enterococcus casseliflavus and E. durans as identified on the basis of 16S rDNA sequence analysis. Weissella strains have also been reported from fermented soybean of North-East India [17] and Korean fermented food, Kimchi [18]. Keem samples were observed to contain 250 9 10 6 cfu/g of amylolytic bacilli.…”
Section: Resultsmentioning
confidence: 90%
“…2 Lactobacilli are commonly used as starter culture of dairy products such as yogurt and traditional cheese. 2 Consumption of native foods containing such indigenous microorganisms possesses many advantages; 3 therefore, the study of probiotics is ubiquitous and many countries have made a great endeavor to isolate probiotic bacteria from natural sea salt, 4 plants, 5 and so from the human gastrointestinal tract, 6 particularly with many endeavors from traditional fermented foods such as cheese. 7 …”
Section: Introductionmentioning
confidence: 99%